Déficit hídrico em tipos de crescimento da soja - Machado Júnior, Carlos Sebastião (2015)
Studies involving the impact of water stress on soybean physiology are abundant, but the studies about determinate and indeterminate growth types are scarce. Considering that the responses of growth types to water stress are of great value to guide drought resistance breeding programs, the aim of this study was to evaluate soybean physiologic parameters and biomass of a determinate and indeterminate growth type under water stress. Six cultivars, been three of determinate growth type (D) and three of indeterminate growth type (I) were submitted to three water stress levels, in the reproductive stage mostly, under greenhouse conditions. The measures of leaf gas exchange, leaf water potential, relative chlorophyll content, chlorophyll A fluorescence and biomass were evaluated during water stress condition, and during two periods, in the morning and in the afternoon. Differences in leaf gas exchanges of both soybean growth types were found between periods of evaluation, the indeterminate growth type (I) presented the greatest values for stomatal conductance, transpiration and CO2 assimilation, leading to higher water consumption, however with no impact on soybean biomass. The great water consumption in the morning leads to lower water potentials at afternoon, when the conditions are more critical. The water stress was not able to change the chlorophyll fluorescence or levels in both soybean growth types.